Paget’s disease of the nipple: dermatologic aspects - Montero, Eustaquio D (Cirugía del Uruguay, 2021)
A revision of the dermatological characieristics of Paget's nipple disease. Includes a description of its clinical characteristics and differential diagnosis with respect to other dermatological lesions of the nipple. To conclude, an account of methods for establishing diagnosis, is given.